Comparison of ultrasound parameters for diagnosis of IUGR - Gangadhar, Pardeshi Yogeshwari; Pillai, Nancy S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: An active approach to the diagnosis of IUGR should be undertaken so that the foetus can be closely monitored and when indicated, be promptly delivered. Methods: Study was conducted at Department of Obstetrics and Gynaecology, Pushpagiri Institute of Medical Sciences, Thiruvalla. All pregnant women whose gestational ages were assessed by ultrasonography in 1st trimester was included in the study. An ultrasonographic biometric evaluation was done between 22-24 weeks and repeated at 32-34 weeks of gestational age and their ratios compared, using standard formulae. Results: We has observed that at 22-24 weeks of gestational age abdominal circumference (AC) has a better sensitivity, specificity, NPV and PPV when compared with femur length (FL), head circumference (HC), FL/AC and HC/AC. AC has got lowest FP and FN with a highest accuracy rate of 83% as compared to FL, HC, FL/AC and HC/AC at 22-24 weeks of gestational age. At 32-34 weeks of gestational age AC remains better in sensitivity, specificity, NPV, PPV, FP and FN values as compared to FL, HC, FL/AC and HC/AC. Conclusions: AC has a better sensitivity, specificity, NPV and PPV for diagnosis of IUGR when compared with FL, HC, FL/AC and HC/AC. AC has got lowest FP and FN with a highest accuracy rate at both 22-24 weeks of gestational age and 32-34 weeks of gestational age. The sensitivity, specificity and accuracy of AC is more at 32-34 weeks of gestation than at 22-24 weeks for diagnosis of IUGR.